ENT 530 Business Model Canvas: McDonald's Company / Nurfarzana Liyana Nawawi ... [et al.] - Nawawi, Nurfarzana Liyana; Mohammad, Nor'ai; Mohd Shah, Alia Natasha; Ghazali, Nur Athirah; Nor Azmi, Nor Alia Aqilah; Mohd Nasir, Nur Adila; Mohd Aris, Nur Syuhada; Saffar, Nur Aqila Najwa; Azali, Nurul Nabilla (2021)
McDonald's Corporation is recognized as a "Centralized, International company" and has become a global company in fast food industries with outlets in 120 countries and over 30,000 restaurants worldwide. McDonald's concentrated on a specific consumer segment, identifying a target demographic, and contrasting marketing tactics to retain consumers. McDonald's characterized its operating system by focusing on uniformity for consistent quality, presupposes an improvement in service delivery, higher satisfaction for customers, cost-effectiveness, superior management of data, and meeting all set targets. McDonald's used three main strategies to expand rapidly into foreign countries: franchising, company-owned restaurants, and joint partnerships. McDonald's management relied on this approach to help in the adoption of a modern way of eating in unfamiliar countries since franchising arrangements account for the bulk of overseas restaurants. McDonald's wanted them to be committed to following the rules and doing new things. The company's implemented, smooth-running supply chain, McDonald's corporate management, and franchisees complement each other, creating an entrepreneurial spirit that adds value, creativity, economies of scale, negotiating power for advertising and buying, as well as new product and process ideas to the company. Furthermore, all involved parties concerned placed a strong focus on adhering to strict quality requirements. McDonald's maintains a firm grip on operations, expense, and quality thanks to its unified, multinational framework. With an ethnocentric management strategy, McDonald’s relies on domestic based logic and attitudes and transfers them to their international outlets and restaurants. Since McDonalds knows their weaknesses, they will strengthen their vulnerabilities so that they are aware of them. McDonalds also can change and create both opportunity and threat. As a result, the company will be able to make better decisions and develop its management skills, resulting in increased productivity.